Notes of statement by Sir William Beveridge to General Council at their meeting on 16 December, 1942 - Beveridge, William Henry Beveridge, Baron, 1879-1963
1942-12-17 1942 1940s 9 pages 3. Another difference was that his scheme porposed [proposed] that for the first thirteen weeks there should be no distinction between compensation for any man who was incapacitated, whether such incapacity was due to ordinary sickness, industrial disease, accident occuring [occurring] inside the factory or outside. The needs were the same whether the accident occurred inside or outside the factory. He did not make any difference for the first thirteen weeks, but when it came to prolonged disability then the injured man got a pension which was proportionate to his earnings which was subject to a minimum and a maximum. It wouldn't be less than the disability benefit for ordinary sickness which was designed to be enough for subsistence. Of course, the rate he suggested was subject to the cost of living, and had been based on the assumption that the cost of living was about 25% above 1928. There was a minimum for the workmen's compensation benefit and he had also included a maximum of £3. per week, irrespective of child allowance, which meant that the industrial pension would range from 56/- to 76/- for a man, wife and three children. His proposal agreed with that of the T.U.C. in keeping benefit related to earnings where there was long incapacity, but not for short incapacity. As soon as a man was injured he would get his money without worry as to whether or not an approved society was to pay it. Meantime enquiries would be made and if it got to the stage of going on pension he would go on according to his earnings. Both the T.U.C. and the Mineworkers had emphasised the fact that the whole cost of industrial accidents and diseases should remain with the employers, and in this respect he drew the Council's attention to paragraph 96 of the Report. His report did not accept that view for three main reasons. If they were pooling the cost on the ground that other industries should pay for the extra dangers of mining, which he though [thought] they should do to some extent but not wholly, it was justifiable to 292/150.5/5/2